Modeling the effect of Shari’ah governance, risk governance and corporate governance in predicting risk-taking behavior of Islamic banks - Ramly, Zulkufly (2019)
This research investigates the relationship between board monitoring, risk committee (RC) independence, Sharia Supervision Boards (SSBs) and risk-taking of Islamic banks (IBs) in Malaysia, Gulf Cooperation Council (GCC) and Southeast Asia (SEA). Independent directors and board size represent board monitoring. This research focuses on the expertise and educational level of SSB members as well as gender diversity in SSBs. Credit risk and insolvency risk represent the level of risk-taking. Using panel data regression techniques to analyze the data for the period of 2009-2015, this study observes that the combinations of (1) board monitoring and SSBs and (2) RC independence and SSBs reduce risk-taking. Further, SSB’s expertise in Sharia and banking-related areas lower credit risk and higher board independence is likely to reduce credit risk when SSBs consist of Sharia advisors with expertise in Sharia and banking-related areas. This study suggests that the resources in terms of valuable experience that SSB advisors bring to IBs combined with the typical board oversight mechanisms such as board independence and RC as suggested by corporate governance literature are beneficial to control risk-taking in IBs. Further, this paper demonstrates that integrating agency theory and resource dependence view in a corporate governance study produces a more meaningful result. In sum, this research shows that greater independent directors monitoring, SSBs expertise, RC independence, gender diverse SSBs are able to control risk-taking activities of IBs.